Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Limit (Lec # 6)

Download as pdf or txt
Download as pdf or txt
You are on page 1of 42

MATH-101 Calculus and Analytical Geometry – 3-0 CHs

By

Irfan Naimat

LIMIT

1
OBJECTIVE

• The concept of a “limit” is the fundamental building block on


which all calculus concepts are based. In this lecture we will
study limits informally, with the goal of developing an
intuitive feel for the basic ideas.

• We will also develop theorems and procedures for calculating


limits.

2
LIMITS AND CONTINUITY

OVERVIEW

The concept of a limit is a central idea that distinguishes


calculus from algebra and trigonometry.

It is fundamental to finding the tangent to a curve or the


velocity of an object.

3
LIMITS AND CONTINUITY

Definition of “LIMIT”:

We write 𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 = 𝐿and say,

“ the limit of 𝑓 𝑥 as 𝑥 approaches a, (→) equals to “L”.

Roughly speaking, this says that the values of f(x) becomes closer
and closer to the number ‘L’ as x approaches to the number ‘a’ (from
either side of a) but note equal to ‘a’ ( i.e. x ≠ a ).

An alternative notation for 𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 = 𝐿is


𝑓 𝑥 → 𝐿as 𝑥 → 𝑎
which is usually read 𝑓 𝑥 approaches ‘L’ as “x” approaches
‘a’.
4
DIRECT SUBSTITUTION PROPERTY

Definition of “LIMIT”:

If f is a polynomial or a rational function and ‘a’ is in the


domain of ‘f’ then 𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 = 𝑓 𝑎 .

Note:
Functions with the direct
substitution property are called
continuous at ‘a’. However not all limits
can be evaluated by direct substitution.

5
CALCULATING LIMITS USING
“THE LIMIT LAWS”
This section presents theorems for calculating limits.

LIMITS LAWS:
1. SUM Rule.
2. Difference Rule.
3. Product Rule.
4. Constant Multiple Rule.
5. Quotient Rule.
6. Power Rule.
7. Constant Function.
8. Identity Function.
Now
Suppose that c is a constant and the limit 𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 and
𝑙𝑖𝑚𝑥→𝑎 𝑔 𝑥 exist. Then
6
THE LIMIT LAWS
1. SUM Rule:
The limit of the sum of two functions is the sum of their limits.
𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 + 𝑔 𝑥 = 𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 + 𝑙𝑖𝑚𝑥→𝑎 𝑔 𝑥
2. DIFFERENCE Rule:
The limit of the difference of two functions is the difference of their
limits.
𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 − 𝑔 𝑥 = 𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 − 𝑙𝑖𝑚𝑥→𝑎 𝑔 𝑥

3. PRODUCT Rule:
The limit of a Product of two functions is the product of their limits.
𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 𝑔 𝑥 = 𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 (𝑙𝑖𝑚𝑥→𝑎 𝑔 𝑥 )
7
4.Constant Multiple Rule:
𝑙𝑖𝑚𝑥→𝑎 𝑐𝑓 𝑥 = 𝑐 𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥
5. Quotient Rule:
𝑓 𝑥 𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥
𝑙𝑖𝑚𝑥→𝑎 = 𝑖𝑓 𝑙𝑖𝑚𝑥→𝑎 𝑔 𝑥 ≠ 0
𝑔 𝑥 𝑙𝑖𝑚𝑥→𝑎 g 𝑥
6. Power Rule:
𝑙𝑖𝑚𝑥→𝑎 ( 𝑓 𝑥 )𝑛 = (𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 )𝑛
where ‘n’ is a +ve integer.
7. Constant Function:
If 𝑓 𝑥 is the constant function 𝒇 𝒙 = 𝒄, then 𝒍𝒊𝒎𝒙→𝒂 𝒄 = 𝒄.
where ‘c’ is any constant number.
8. Identity Function:
If 𝑓 𝑥 is the identity function 𝒇 𝒙 = 𝒙, then for any value of
‘a’ 𝑙𝑖𝑚𝑥→𝑎 𝑥 = 𝑎.
8
Remark

1. 𝑙𝑖𝑚𝑥→𝑎 𝑥 𝑛 = 𝑎𝑛 , where ‘n’ is a positive integer.

2.𝑙𝑖𝑚𝑥→𝑎 𝑛 𝑥 = 𝑛
𝑎, where ‘n’ is a positive integer.

3. 𝑙𝑖𝑚𝑥→𝑎 𝑛 𝑓(𝑥) = 𝑛 𝑙𝑖𝑚𝑥→𝑎 𝑓(𝑥),

where ‘n’ is a positive integer

9
Examples
Example # 1Find 𝑙𝑖𝑚𝑥→𝑐 (𝑥3 + 4𝑥2 – 3)
Solution
𝑙𝑖𝑚𝑥→𝑐 (𝑥3 + 4𝑥2 – 3) = 𝑙𝑖𝑚𝑥→𝑐 𝑥 3+ 𝑙𝑖𝑚𝑥→𝑐 4 𝑥2 − 𝑙𝑖𝑚𝑥→𝑐 3
(Using Sum and Difference Rule)
= c3 + 4𝑐2 – 3.
𝑥4 + 𝑥2 – 1
Example # 2Find 𝑙𝑖𝑚𝑥→𝑐 𝑥2 +5
Solution
𝑥4 + 𝑥2 – 1 𝑙𝑖𝑚𝑥→𝑐 (𝑥4 + 𝑥2 – 1)
𝑙𝑖𝑚𝑥→𝑐 = Quotient Rule
𝑥2 +5 𝑙𝑖𝑚𝑥→𝑐 (𝑥2 +5)

𝑙𝑖𝑚𝑥→𝑐 (𝑥4 )+𝑙𝑖𝑚𝑥→𝑐 (𝑥2 )−𝑙𝑖𝑚𝑥→𝑐 (1)


= (Sum & Difference Rule)
𝑙𝑖𝑚𝑥→𝑐 (𝑥2 )+𝑙𝑖𝑚𝑥→𝑐 (5)
Power Rule
(𝑙𝑖𝑚𝑥→𝑐 𝑥 )4 + (𝑙𝑖𝑚𝑥→𝑐 𝑥 )2 − (𝑙𝑖𝑚𝑥→𝑐 1) 𝑐4 + c 2 − 1
= 2
=
(𝑙𝑖𝑚𝑥→𝑐 𝑥 ) + (𝑙𝑖𝑚𝑥→𝑐 5) 𝑐2 + 5
10
Example # 3Find 𝑙𝑖𝑚𝑥→ −2 4𝑥2 − 3

Solution𝑙𝑖𝑚𝑥→ −2 4𝑥2 − 3 = 𝑙𝑖𝑚𝑥→ −2 4𝑥2 − 3

= 𝑙𝑖𝑚𝑥→ −2 4𝑥2 ) − 𝑙𝑖𝑚𝑥→ −2 (3

= 4 (𝑙𝑖𝑚𝑥→−2 𝑥)2 − 𝑙𝑖𝑚𝑥→−2 3 = 4 −2 2 −3

= 4(4) − 3 = 16 − 3 = 13

11
THEOREM
1. Limits of Polynomials can be found by Substitution
If𝑃 𝑥 = an 𝑥n +an − 1𝑥n −1 + ⋯ + a0
𝑙𝑖𝑚𝑥→𝑐 𝑃 𝑥 = 𝑃 𝑐 = an 𝑐n +an − 1𝑐n−1 + ⋯ + a0
2. Limits of Rational functions can be found by substitution if
the limit of the Denominator is not zero.
If 𝑃 𝑥 and Q 𝑥 are polynomials and Q 𝑐 ≠0 then

𝑃 𝑥 𝑃 𝑐
𝑙𝑖𝑚𝑥→𝑐 =
𝑄 𝑥 𝑄 𝑐

12
Examples (Limit of Rational Function)
𝑥3 +4𝑥2−3
Example # 1 Find 𝑙𝑖𝑚𝑥→−1
𝑥2 +5
Solution
𝑥3 +4𝑥2 − 3 𝑙𝑖𝑚𝑥→−1 (𝑥3 +4𝑥2 − 3)
𝑙𝑖𝑚𝑥→−1 =
𝑥 +5
2 𝑙𝑖𝑚𝑥→−1 (𝑥2 +5)

(−1)3 +4(−1)2 − 3 0
= 2
= =0
(−1) +5 6
2𝑥 2 +1
Example # 2 Find 𝑙𝑖𝑚𝑥→2 2
𝑥 +6𝑥−4
Solution
2𝑥 2 + 1 𝑙𝑖𝑚𝑥→2 (2𝑥 2 + 1)
𝑙𝑖𝑚𝑥→2 2 =
𝑥 + 6𝑥 − 4 𝑙𝑖𝑚𝑥→2 (𝑥 2 + 6𝑥 − 4)

2(2)2 + 1 9 3
= 2
= =
(2) + 6(2) − 4 12 4 13
Evaluate the following Limits.
𝑥 3 +2𝑥 2 −1
Question # 1𝑙𝑖𝑚𝑥→−2
5−3𝑥

𝑥 3 + 2𝑥 2 − 1 𝑙𝑖𝑚𝑥→ −2 (𝑥 3 + 2𝑥 2 − 1)
𝑙𝑖𝑚𝑥→ −2 =
5 − 3𝑥 𝑙𝑖𝑚𝑥→ −2 (5 − 3𝑥)

𝑙𝑖𝑚𝑥→ −2 𝑥 3 + 𝑙𝑖𝑚𝑥→ −2 2𝑥 2 − 𝑙𝑖𝑚𝑥→ −2 (−1)


=
𝑙𝑖𝑚𝑥→ −2 5 − 𝑙𝑖𝑚𝑥→ −2 (3𝑥)

(−2)3 +2(−2)2 −1 −1
= =
5 − 3(−2) 11

14
Eliminating Zero (Denominators Algebraically)
• If the denominator of the rational function is zero, canceling
common factors in the numerator and denominator may reduce
the fraction to one whose denominator is no longer zero at ‘c’.

• If this happens, we can find the limit by substitution in the


simplified fraction.
𝑥 2 +𝑥−2
Question # 1Evaluate 𝑙𝑖𝑚𝑥→1 2
𝑥 −𝑥
2
𝑥 +𝑥−2
Solution 𝑙𝑖𝑚𝑥→1 2
𝑥 −𝑥
We can’t substitute 𝑥 = 1, because it makes the denominator zero
(𝑥 − 1)(𝑥 + 2) (𝑥 + 2)
𝑙𝑖𝑚𝑥→1 = 𝑙𝑖𝑚𝑥→1
𝑥 (𝑥 − 1) 𝑥

𝑙𝑖𝑚𝑥→1 (𝑥 + 2) 3
= = =3
𝑙𝑖𝑚𝑥→1 𝑥 1
15
𝑥 2 +𝑥−6
Question # 2 Evaluate 𝑙𝑖𝑚𝑥→2
𝑥−2

𝑥 2 +𝑥−6
Solution𝑙𝑖𝑚𝑥→2
𝑥−2

𝑥 2 + 𝑥 − 6 𝑙𝑖𝑚𝑥→2 (𝑥 2 + 𝑥 − 6)
𝑙𝑖𝑚𝑥→2 =
𝑥−2 𝑙𝑖𝑚𝑥→2 (𝑥 − 2)
(2)2+2 −6
= (Denominator vanishes)
2−2
Now consider,

𝑙𝑖𝑚𝑥→2 (𝑥 2 + 𝑥 − 6) 𝑙𝑖𝑚𝑥 → 2 (𝑥 + 3)(𝑥 − 2)


=
𝑙𝑖𝑚𝑥→2 (𝑥 − 2) 𝑙𝑖𝑚𝑥 → 2 (𝑥 − 2)

= 𝑙𝑖𝑚𝑥→ 2 𝑥 + 3 = 𝑙𝑖𝑚𝑥→ 2 2 + 3 = 5

16
Examples

𝑥2−1
Question # 1Find 𝑙𝑖𝑚𝑥→ 𝟏 Try Yourself Ans = 2
𝑥−1

𝑥2−6𝑥+9
Question # 2Find 𝑙𝑖𝑚𝑥→ 3 Try Yourself Ans = 0
𝑥−3

2𝑥+8
Question # 3Find 𝑙𝑖𝑚𝑥→ −4 2 Try Yourself Ans = 0
𝑥 +4𝑥−12

𝑥2−3𝑥−10
Question # 4Find 𝑙𝑖𝑚𝑥→ 5 2 Try Yourself
𝑥 −10𝑥+25

Answer = doesn’t exist (after simplification)

3+ℎ 2−9
Question # 5Find 𝑙𝑖𝑚ℎ→ 0 Try Yourself Ans = 6

17
Creating & Canceling Common Factor / Limits Involving Radicals
2+ℎ − 2
Example: Find 𝑙𝑖𝑚ℎ→ 0

SolutionWe cannot find the limit by substituting ℎ = 0 and the numerator
and denominator don’t have obvious factors. However, we can create a
common factor in the numerator by multiplying it (and the denominator)
by the so-called conjugate expression. 2 + ℎ − 2 obtained by
changing the sign b/w the square roots.
Now
2+ℎ − 2 2+ℎ − 2 2+ℎ + 2
=
ℎ ℎ 2+ℎ + 2
2+ℎ−2
=
ℎ( 2+ℎ + 2 )
ℎ 1
= =
ℎ( 2+ℎ + 2 ) 2+ℎ + 2 18
Examples

𝑥−1
Question # 1: Find 𝑙𝑖𝑚 𝑥→1 Try Yourself Ans = 2
𝑥 −1

𝑡2+9 −3 1
Question # 2: Find lim 𝑡→0 Try Yourself Ans =
𝑡2 6

𝑥2+100 −10 1
Question # 3: Find 𝑙𝑖𝑚 𝑥→0 Try Yourself Ans =
𝑥2 20

19
Left-Hand Limit & Right-Hand Limit
or
Limits of a Piece-wise Defined Functions
For functions that are defined piece-wise, a two-sided limit at a point
where the formula changes is best obtained by first finding the one-
sided limits at that point.
Theorem
A function 𝑓 𝑥 has a limit as 𝑥 approaches ‘𝑐’ if and only if it has left
hand and right-hand limits there and these one-sided limits are equal:

𝑙𝑖𝑚 𝑥→ 𝑎 𝑓 𝑥 = 𝐿

𝑙𝑖𝑚𝑥 → a+𝑓 𝑥 = 𝐿 and 𝑙𝑖𝑚 𝑥→𝑎− 𝑓 𝑥 = 𝐿

RIGHT HAND LIMIT LEFT HAND LIMIT


20
Example:
Evaluate 𝑙𝑖𝑚 𝑥→ 0 | 𝑥 | = 0
Solution Since according to the definition of | 𝑥 | we have

𝑥 𝑥≥0
𝑓 𝑥 = 𝑥 =
−𝑥 𝑥<0

𝑙𝑖𝑚 𝑥→ 0− 𝑓 𝑥 = 𝑙𝑖𝑚 𝑥→ 0− 𝑥 = 𝑙𝑖𝑚 𝑥→ 0− −𝑥 = 0

𝑙𝑖𝑚𝑥 → 0+𝑓 𝑥 = 𝑙𝑖𝑚𝑥 → 0+ 𝑥 = 𝑙𝑖𝑚 𝑥 → 0+ 𝑥 = 0

⇒ 𝐿. 𝐻. 𝐿 = 𝑅. 𝐻. 𝐿
so
𝑙𝑖𝑚 𝑥→0 | 𝑥 | = 0 exist.
21
𝑥
Example: Proof that 𝑙𝑖𝑚 𝑥→ 0 = 0doesn’t exist
𝑥
Solution:Since according to the definition of | 𝑥 | we have
𝑥 𝑥≥0
|𝑥| =
−𝑥 𝑥<0

(−𝑥)
𝑙𝑖𝑚 𝑥→ 0 −
= 𝑙𝑖𝑚 𝑥→ 0− −1 = −1
𝑥

+
(𝑥)
𝑙𝑖𝑚 𝑥 → 0 = 𝑙𝑖𝑚 𝑥 → 0+ 1 = 1
𝑥

⇒ 𝐿. 𝐻. 𝐿 ≠ 𝑅. 𝐻. 𝐿
𝑥
So 𝑙𝑖𝑚 𝑥→ 0 = 0 doesn’t exist
𝑥
22
Examples
Question #1Evaluate left- and right-hand limit of the function
defined by
𝑥−3
𝑓 𝑥 =൝ 𝑥 ≠ 3 at 𝑥 = 3
𝑥−3
0 𝑥=3
Solution:Try yourself
Question # 2Let
1
𝑥 < −2
𝑓 𝑥 = 𝑥+2 −2 < 𝑥 ≤ 3
𝑥2 − 5
𝑥>3
𝑥 + 13
Find
a) 𝑙𝑖𝑚 x→ −2 𝑓 𝑥
b) 𝑙𝑖𝑚 𝑥→ 0 𝑓 𝑥
c) 𝑙𝑖𝑚 𝑥→ 3 𝑓 𝑥 23
Solution: 2(a)
We will determine the stated two-sided limit by first considering the
corresponding one-sided limits. For each one-sided limit, we must
use that part of the formula that is applicable on the interval over
with 𝑥 −varies.
For example, as x approaches −2 from the left, the applicable part of
the formula is
1
𝑓 𝑥 =
𝑥+2
and as 𝑥 approaches −2 from the right, the applicable part of the
formula near −2 is
𝑓(𝑥) = 𝑥2 − 5
1
Thus 𝑙𝑖𝑚 𝑥→ −2 𝑓 𝑥 = 𝑙𝑖𝑚 𝑥→ −2 𝑥+2 = −∞
− −

𝑙𝑖𝑚 𝑥→ −2+ 𝑓 𝑥 = 𝑙𝑖𝑚 𝑥→ −2+ 𝑥2 − 5 = −1


Thus it follows that 𝑙𝑖𝑚 x→ −2 𝑓 𝑥 doesn’t exist.
24
Solution: 2(b)

The applicable part of the formula is 𝑓 𝑥 = 𝑥2 − 5 on both


sides of 0, so there is no need to consider one-sided limits
here.
𝑙𝑖𝑚 𝑥→ 0 𝑓 𝑥 =lim𝑥 → 0 𝑥2 − 5 = 0 − 5 = −5

Solution: 2(c)

Using the applicable parts of the formula for 𝑓 𝑥 We obtain

𝑙𝑖𝑚 𝑥→ 3− 𝑓 𝑥 = 𝑙𝑖𝑚 𝑥→ 3− 𝑥2 − 5 = 9 − 5 = 4

𝑙𝑖𝑚 𝑥→ 3+ 𝑓 𝑥 = 𝑙𝑖𝑚 𝑥→ 3+ 𝑥 + 13 = 3 + 13 = 4
Since the one-sided limits are equal so we have
𝑙𝑖𝑚 𝑥→ 3 𝑓 𝑥 =4
25
Theorem
If 𝑓 𝑥 and 𝑔 𝑥 are two functions. If 𝑓 𝑥 ≤ 𝑔 𝑥 when x
is near a (except possibly at a) and the limit of ‘𝑓 ′ and ‘𝑔’
both exist as 𝑥 approaches ‘𝑎’ then

𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 ≤ 𝑙𝑖𝑚𝑥→𝑎 𝑔 𝑥

SQUEEZE THEOREM
(Sandwich or Pinching Theorem)

If 𝑓 𝑥 ≤ 𝑔 𝑥 ≤ ℎ 𝑥 when x is near a (except possibly at a)


and
𝑙𝑖𝑚𝑥→𝑎 𝑓 𝑥 = 𝑙𝑖𝑚𝑥→𝑎 ℎ 𝑥 = 𝐿
then
𝑙𝑖𝑚𝑥→𝑎 𝑔 𝑥 = 𝐿
26
1
Example:Show that 𝑙𝑖𝑚 𝑥→ 0 𝑥2 𝑠𝑖𝑛 =0
𝑥
Solution:First note that we cannot use
1 1
𝑙𝑖𝑚 𝑥→ 0 𝑥2 𝑠𝑖𝑛 = (𝑙𝑖𝑚 𝑥→ 0 𝑥2 ) (𝑙𝑖𝑚 𝑥→ 0 𝑠𝑖𝑛 ) because
𝑥 𝑥
1
𝑙𝑖𝑚 𝑥→ 0 𝑠𝑖𝑛 doesn’t exist. However
𝑥
−1 ≤ 𝑠𝑖𝑛 𝑥 ≤ 1
1
−1 ≤ 𝑠𝑖𝑛 ≤1
𝑥
2 2
1
−𝑥 ≤ 𝑥 𝑠𝑖𝑛 ≤ 𝑥2
𝑥
We know that
𝑙𝑖𝑚 𝑥→ 0 𝑥2 = 0 and 𝑙𝑖𝑚 𝑥→ 0 (−𝑥2) = 0
1
Taking 𝑓 𝑥 = −𝑥2, 𝑔 𝑥 = 𝑥2 𝑠𝑖𝑛 and ℎ 𝑥 = 𝑥2
𝑥
So using SQUEEZE THEOREM
1 27
𝑙𝑖𝑚 𝑥2 𝑠𝑖𝑛 =0
𝑥2 𝑥2
Example: Given that 1 − ≤ 𝑢 𝑥 ≤ 1 +
4 2
for all 𝑥 ≠ 0.Find 𝑙𝑖𝑚 𝑥→ 0 𝑢 𝑥 ,no matter how
complicated 𝑢 is.

Solution:
𝑥2
𝑙𝑖𝑚 𝑥→ 0 1− =1−0=1
4

𝑥2
𝑙𝑖𝑚 𝑥→ 0 1+ =1+0=1
2
The sandwich theorem implies that

𝑙𝑖𝑚 𝑥→ 0 𝑢 𝑥 = 1
28
Exercises

29
30
31
32
33
34
35
36
37
38
39
40
41
42

You might also like